Computational Intelligence for Missing Data Imputation, Estimation, and Management : Knowledge Optimization Techniques - Marwala, Tshilidzi, 1971-, author 632768; Gale Group (Online service) 651863 (Hershey, PA : Information Science Reference, 2009)
"This book is for those who use data analysis to build decision support systems, particularly engineers, scientists and statisticians"--Provided by publisher